The effective factors in the decision making component of purchase management of Medical Equipment in hospitals affiliated to Tehran University of Medical Sciences - Azam Lari; Kamran Hajinabi; Ali Komeili; Leila Riahi (Tehran University of Medical Sciences, 2020)
Bachground: The use of optimal purchasing methods in the medical equipment sector, along with the implementation of state laws and regulations by the government, can serve as a way to move towards smart purchases. To be raised. The aim of investigating the factors affecting the decision making of purchasing capital equipment in hospitals affiliated to Tehran University of Medical Sciences. Materials and Methods: In this applied research, which was conducted in the year 2017, the statistical population of the study were directors, heads and supervisors of the diagnostic and therapeutic sections and medical equipment of all hospitals, and managers and experts of medical equipment of the University of Medical Sciences who were 631 They formed. Data gathering tool was a researcher-made questionnaire. After verifying their validity and reliability, the data were collected and analyzed using SPSS software. Results: The most effective variables of the actual price of capital equipment at purchase time with a regression coefficient of 0.368 and against the least effective variable in this area is the competitive or exclusive sale of the market with a regression coefficient of 0.162. Conclusion: Therapeutic centers to purchase capital equipment should use standard decision-making criteria. Considering the sensitive role of identifying and selecting the best brand for the purchase of equipment, as well as the costs that these purchases bring to the health system, the use of quantitative and qualitative criteria as well as the use of experts is very important, in this way, equipment Provides economical and quality services to provide the right services.